Removal of Copper from Water by Decaying Tamrix gallica Leaves - R. Zaggout, Farid (Asian Journal of Chemistry, 2010)
Uptake of copper from aqueous solution by Tamrix gallica leaves has been studied. The effect of several factors on both rate and amount of this uptake has been investigated. These factors include concentration of copper, concentration of leaves, pH, competing ions, drying leaves and grinding leaves. The pattern of curves showing the loss of copper from solution has been explained. Applicability of the Freundlich adsorption isotherm on the present results has been examined and the parameters of this isotherm have been calculated. The order of reaction between copper ion and Tamrix gallica leaves has been determined and a mechanism for this reaction has been suggested.